Utilization of dried mushroom powder for development of mushroom fortified biscuits - Desayi, D B; Kukanoor, L H; Patil, C P; Shirur, M; Shivakumar, B B (Mushroom Research, 2012)
A study was conducted to develop the mushroom fortified biscuits as influenced by fortification of different levels of mushroom powder and artificial flavours. Mushroom fortified biscuits were prepared by adding mushroom powder to the biscuit recipe at 5, 10 and 15 per cent concentrations along with addition of strawberry and vanilla flavours at each level, whereas biscuits prepared only with bakery recipe were kept as control. Among different treatments, 10 per cent mushroom powder along with 0.2 per cent vanilla flavour recorded highest scores for organoleptic parameters like colour and appearance, flavour, crispness, taste and overall acceptability even upto 30 days of storage. Whereas, it was at par with fortification of 10 per cent mushroom powder along with 0.2 per cent strawberry flavour. Fortification with 10 per cent mushroom powder along with 0.2 per cent vanilla or strawberry flavour in bakery recipe was better for preparation of mushroom fortified biscuits.